Illicit financial flows in low- and middle-income countries: A hindrance to human development. - Ortega-Aguaza, Bienvenido; Sanjuán-Solís, Jesús Carlos; Casquero-Tomás, Antonio (My University, 2018)
Illicit financial flows (IFFs) are cross-border transfers of funds that are illegally earned, transferred, or utilized. Although it is widely recognised that these flows drain the scarce public resources available to finance the provision of public services and investments, there are few contributions on the effects of IFFs on human development. In this context, the main aim of this paper is to analyse empirically the relationship between IFFs and human development. This study used annual data for 56 low- and middle-income countries for the period 2002-2013 (provided by the UN’s Human Development Index (HDI), the World Bank, Transparency International, and Global Financial Integrity) and employed econometric methods to quantify the impact of the relative size of IFFs on the HDI. The main result was that the total effect of an annual 10 percentage point increase in the ratio of IFFs to total trade would imply a 20.2 point decrease in HDI level as a long run effect. Thus, research findings suggest the urgent need to reduce IFFs as part of development policy in these countries.
Keywords: Finanzas